Aktivitas Antioksidan Ekstrak dan Fraksi Daun Manggis (Garcinia mangostana) terhadap DPPH (1,1-Difenil-2-Pikrilhidrazil) - Ghani Nurfiana; Lukito Mindi; Masyitah Novia (Jurnal Farmasi Indonesia, 2017)
Antioxidant is very important to keep human’s health because it can scavenge free radical. Garcinia mangostanaL. which is used by people as traditional herbal medicine and it has traditional name mangosteen is known contain of flavonoid, tannin and saponin. The aim of the experiment was to find out the antioxidant activity of extracts and fractions of mangosteen folium against the DPPH radicals (1,1-diphenyl-2-picrylhydrazyl) to determine the IC50 and classes of compounds that play a role in antioxidant activity assay.Mangosteen leaves were extracted by maceration method using 96% ethanol. Extract was partitionedwith water and n-hexane, and then with ethyl acetate. The antioxidant activity of fraction was tested against DPPH radicals. The test was conducted in 5 series of concentrations by adding 4.0 ml test solutions with 1.0 mlDPPH 0.45 mM. The radicals scavenging activity was measured with spectrophotometer at 517 nm wavelength anddetermined the IC50 value. The experiment used Rutin as positive control.The identification of the class of compounds can be carried out using the Thin Layer Chromatography (TLC) method whose results can be identified by spray reagents or compared with the standard standard. The result of the experiment showed that Mangosteen folium had antioxidant activity with IC50 of ethanol extract, n-hexane fraction, ethyl acetate fraction and water fraction: 17.64 μg / ml, 45.36 μg / ml, 13.71 μg / ml, 12.10 μg / ml respectively. The water fraction has the strongest activity compare to the other with the IC50 is almost near often Rutin’s IC50 is 15.24 μg as the positive control. Extracts and fractions of TLC with various spotting agents contain a class of compounds: flavonoids, saponins and steroids